Mapping Capital Budgeting in the Private Sector: A Systematic Literature Review and Future Research Study - Groda, Selvi Permata; Anggraini, Afriska Yuni; Norisnita, Muazila; Waspada, Ikaputera; Rihidima, Lidya Veronica Christy (GoAcademica Research & Publishing, 2025)
This research investigates the critical role of capital budgeting in achieving corporate success and sustainability in a dynamic global economy. The main focus is on complex financial evaluation techniques for making long-term investment decisions and their impact on firm performance and growth. In addition, this study analyzes trends in the use of capital budgeting methods in different countries, including the implications of changes in executive compensation contracts. In addition, the challenges faced by companies in evaluating investment projects, including the need for more sophisticated analyses such as real options, are an important focus of this research. Using the systematic literature review (SLR) method, this study identifies and analyzes relevant articles related to the evolution of research publication approaches and various capital budgeting techniques. The results of this study are expected to provide a deeper understanding of the current trends and practices in capital budgeting decision-making in the private sector and formulate relevant research questions to guide future studies in this area.